THE ROLE OF LIBRARIES AND INFORMATION CENTERS IN PROVIDING INFORMATION RESOURCES FOR ISLAMIC ECONOMICS, BANKING, AND FINANCE TO ACHIEVE SUSTAINABLE DEVELOPMENT IN NIGERIA - Dada, Kayode Sunday John; Ajayi, Emmanuel Oluwaseun; Hamza, Jumare Mohammed; Muhammad, Amina (Asian Journal of Islamic Economic Studies, 2026)
This study examines how libraries and information centers contribute to sustainable development in Nigeria through the provision of information resources for Islamic economics, banking, and finance. The research adopted a quantitative design with 338 respondents comprising librarians, Islamic bankers, economists, and finance professionals. Data were collected through structured questionnaires and analyzed using descriptive statistics including frequencies, percentages, mean scores, and standard deviations. Findings revealed that libraries provide diverse information resources including books, journals, databases, and digital materials to support Islamic finance education and practice. The mean score of 3.78 indicated strong agreement that these resources contribute significantly to sustainable development goals. However, challenges such as inadequate funding, limited specialized collections, poor infrastructure, staff training gaps, and low awareness among users were identified. The study recommends increased budgetary allocation, acquisition of specialized materials, infrastructure development, continuous staff training, awareness campaigns, partnerships with Islamic financial institutions, digitization initiatives, and policy formulation to strengthen the role of libraries in advancing Islamic finance knowledge for sustainable development in Nigeria..